Efektivitas Penegakan Hukum Terhadap Tindak Pidana Narkotika di Kepolisian Resor Sidrap - Soetarmi, Soetarmi (CV. Social Politic Genius (SIGn), 2023)
This study aims to determine law enforcement against narcotics crime in Sidrap Regency, Sulawesi Province and the factors that influence it. The type of research used is empirical legal research with quantitative descriptive nature. This research was conducted in the jurisdiction of the Sidrap Police. The data collection techniques used in this research were questionnaires, documentation, and literature study. The data analysis technique used is quantitative data analysis techniques. The results showed that law enforcement against narcotics crime in Sidrap Regency is less effective because every year narcotics crime continues to increase. Factors affecting law enforcement against narcotics crime in Sidrap Regency include: Legal Substance Factors; Police Apparatus Resource Factors; Facility and Infrastructure Factors; and Public Legal Awareness Factors. The authorities are expected to be more proactive in law enforcement related to narcotics crime because narcotics crime is included in the Extra Ordinary Crime. Furthermore, community participation is needed in the eradication of narcotics crime, so that if there is abuse of narcotics in the vicinity, they can report to the competent authorities so that they can take action in accordance with applicable legal provisions.